DESIGNING LIGHTING ENVIRONMENTS FOR MUSEUM AND ART GALLERY INTERIORS (Neo Scientific Peer Reviewed Journal, 2026)
The article examines the features of interiors intended to house museum exhibits, studies the lighting characteristics of these interiors, as well as methods for the correct use of artificial and natural lighting for museums and art galleries.